Contra Celsum : libri VIII - Origen. (Vigiliae Christianae, Supplements, 2001)
The giant treatise Contra Celsum is Origen's main and longest work. It is of significance for both Greek Patristics and Ancient Philosophy. However, the extant text of the treatise is lacunose and corrupt. Two outstanding editions - by Paul Koetschau (1899) and Marcel Borret (1967-1969) - are not critical enough. The editor tried to restore Origen's original text and presents the reader with a reasonably reliable text.